Pengendalian Waktu Efektif Bulldozer CAT D8R Rental Untuk Meminimalisasi Biaya Operasional Di PT Bukit Asam Tbk Unit Pelabuhan Tarahan Bandar Lampung - Ronaldo Davinci; Dedi Yulhendra (Departemen Teknik Pertambangan FT UNP, 2019)
Abstract. The D8R CAT Bulldozer is one type of mechanical device used for port operations through a rental system between PT Bukit Asam Tbk Tarahan Port Unit and PT Lematang. The high hours of the Bulldozer road will certainly have an impact on operational costs as well as the cost of the rental unit itself and the consumption of fuel oil. It is hoped that using the Overall Equipment Effectiveness (OEE) method in this case can be a solution to detect the main causes of the high hours of bulldozers. Determine the magnitude of each factor of the six major losses that affect the effectiveness of Bulldozer Performance, and analysis of the factors that are the top priority as a basis for improvement.Keywords: Effective Time, Overall Equipment Effectiveness (OEE), Six Big Losess, SPSS, and Bulldozer CAT D8R